Diagnostic value of plasma heat shock protein 90α and inflammatory markers in prostate cancer - Zhang, Weiwei; Miao, Yajun; Liu, Lisheng (Frontiers in Oncology, 2026)
ObjectiveTo assess plasma levels of heat shock protein 90α (Hsp90α) and inflammatory markers, and evaluate their diagnostic potential in prostate cancer (PCa).Patients and methodsPatients were divided into two groups based on histopathological diagnosis: PCa group and benign prostatic disease group. The levels of plasma Hsp90α and inflammatory markers were compared between groups. Diagnostic performance was evaluated using receiver operating characteristic (ROC) curve analysis. Bioinformatics analysis (Gene Set Enrichment Analysis, GSEA) was further performed to explore the potential Hsp90α-related signaling pathways in PCa.ResultsPlasma Hsp90α levels were significantly higher in PCa patients compared to benign prostatic disease patients (102.8 ± 89.77vs.62.57 ± 34.82 ng/mL, p < 0.001), while PLT (213 ± 58.95vs.266 ± 70.62 *109/L, p < 0.05) and platelet-to-neutrophil ratio (PNR, 62.48 ± 24.01vs.74.33 ± 25.19, p < 0.05) were significantly lower. Plasma Hsp90α levels showed strong correlations with the M stage (p < 0.001), N stage (p < 0.01) and Clinical stage (p < 0.001), PNR was negatively correlated with M stage (p < 0.01), decreasing with tumor progression. ROC curve analysis revealed moderate diagnostic value for Hsp90α (AUC = 0.661), PLT (AUC = 0.601), and PNR (AUC = 0.590). GSEA indicated that significant correlation between Hsp90 levels and protein secretion-related pathways and cell cycle regulation signaling pathways.ConclusionsIn summary, this study demonstrates the potential clinical utility of plasma Hsp90α as an auxiliary diagnostic biomarker for PCa, particularly in advanced or metastatic disease. Furthermore, we are the first to report the diagnostic and distant metastasis risk assessment potential of PNR in PCa. Notably, diagnostic models integrating Hsp90α and PNR with prostate-specific antigen (PSA) exhibited superior performance compared to PSA alone, suggesting their complementary role. Through integrated bioinformatics analyses, we have elucidated the molecular mechanisms by which Hsp90α drives PCa progression. These findings provide novel mechanistic insights into the pathophysiology of PCa and establish a foundation for developing future diagnostic strategies and targeted therapies focusing on Hsp90α or its associated pathways.